Analisis keterampilan bercerita berbasis video peserta didik kelas v sekolah dasar - Budiarti, Meilani Rayyana; Rukayah, Rukayah; Daryanto, Joko (Didaktika Dwija Indria, 2021)
Abstract. This aim of this research is to describe the ability to video-based storytelling skills in grade V SDN Wirotaman in the academic year 2020/2021. The method used in this research is descriptive qualitative. The data source of this research is the fifth grade students of SDN Wirotaman as many as eight children as the research sample taken by using purposive sampling technique. The technique of collecting data was carried out by interviews, and document analysis by testing the validity of the data using triangulation techniques. The data were analyzed using the Miles and Huberman data analysis models. The results of this study indicate that students are able to tell interactive video-based stories by fulfilling the specified indicators. The results of this study also encourage teachers to determine effective strategies, models, and methods so as to improve students' video-based storytelling skills.